Uma análise do projeto pedagógico da licenciatura em informática do Ifap à luz das recomendações da sociedade brasileira de computação - SILVA, José Dario Pintor da (Instituto Federal do Amapá, 2021)
ABSTRACT: The construction of the Curriculum Content Plan is very important for undergraduate courses. It is in this document t hat we find the purpose of the course, the profile of the graduate, the axes of content formation, the content itself, the expected skills and competences etc., that is, it allowed to form a graduate with a solid and consistent professional profile. The Br azilian Society of Computing (Sociedade Brasileira de Computação), prepared the Formation Reference for Undergraduate Courses in Computer Science, based on the National Curriculum Guidelines, which serves as a guide for the construction of the Pedagogical Curriculum Plan for the area. This article aims to analyze the Pedagogical Curriculum Plan of Computer Science Degree Course at Instituto Federal do Amapá under light of the recommendations of the Brazilian Computer Society. The result of the analysis poin ts out that the Pedagogical Curriculum Plan of the Computer Science Degree Course is in line with what the Formation Reference of the Brazilian Computer Society recommends regarding the contents, practices as a curricular component, Course Conclusion Work , however it is not assertive how much the skills and competences of each curricular component should have.